Influence of Price, Promotion, and Product Quality on Boba Drink Purchase Decisions Through Recommendations as Intervening Variables (Boba Qiuqiunian Drinking Business Case Study) - Sari, Preti Intan; Hermain, Hendra; Daulay, Aqwa Naser (Quantitative Economics and Management Studies, 2024)
This research aims to analyze the influence and relationship between five variables, namely price, promotion, product quality on purchasing decisions through recommendations. This type of research is quantitative research. This research was conducted at the QIUQIUNIAN Boba Beverage Company. Sampling used the non-probably sampling method with a remote sampling technique of 100 respondents. Data obtained by distributing questionnaires was then analyzed using multiple linear regression tests and hypothesis testing using SPSS IBM version 22. Based on the research results it can be concluded that: Price has a significant effect on recommendations, Promotion has a significant effect on recommendations, Product quality has no significant effect on recommendations, Purchasing decisions have a significant effect on recommendations.